Investigation of Cement-Emulsified Asphalt in Plastic Concrete. (3rd April 2018) - Yan, Xiaohu; Wang, Zaiqin; Rao, Meijuan; Li, Mingxia
Abstract : The mechanical, mesodamage, and the microproperties of cement-emulsified asphalt concrete have been investigated by computed tomography (CT), scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric analysis (TG) in this work. Emulsified asphalt delayed the hydration of cement, making the early compressive strength of concrete develop slowly. However, the concrete compressive strength increased rapidly with the demulsification of emulsified asphalt. The damage stages of condense, expansion of volume, rapid crack propagation, and damage by real-time scanning have been observed. The CT mean value of the place near the lower end face suffered a larger decline but a smaller decline to the upper part of the sample. The evolution of concrete suffering damage to failure is a gradual development process, and no sharp expansion of brittle failure. The unhydrated cement, incorporation asphalt, fibrous C–S–H gel, CH, needle-shaped ettringite, and other hydration products were interwoven to constitute emulsified asphalt-cement paste, forming a spatial structure.